Factors influencing satisfaction on YouTube usage among students - Nazari, Nur Syahirah; Wok, Saodah (2018)
YouTube is one of the social networking sites using a video and it is very attractive among the young generation especially students. Therefore, this study aims to determine the relationship among perception, attitude, behavior, impact and satisfaction of YouTube usage and to identify the best predictor for YouTube satisfaction. Uses and Gratification Theory is used to explain the satisfaction with regards to YouTube usage among students. This study employs a quantitative research design using the survey method with questionnaire as its research instrument for data collection. A total of 229 respondents participated in the study. The results show that students have a positive perception, attitude, behavior, impact and satisfaction with the YouTube. There are positive relationships among the variables and the best predictor for satisfaction of YouTube usage is the impact of YouTube on the students.